Independent Evolution of Sex Chromosomes and Male Pregnancy–Related Genes in Two Seahorse Species. (29th December 2022) - Long, Xin; Charlesworth, Deborah; Qi, Jianfei; Wu, Ruiqiong; Chen, Meiling; Wang, Zongji; Xu, Luohao; Fu, Honggao; Zhang, Xueping; Chen, Xinxin; He, Libin; Zheng, Leyun; et al.
Abstract: Unlike birds and mammals, many teleosts have homomorphic sex chromosomes, and changes in the chromosome carrying the sex-determining locus, termed "turnovers", are common. Recent turnovers allow studies of several interesting questions. One question is whether the new sex-determining regions evolve to become completely non-recombining, and if so, how and why. Another is whether (as predicted) evolutionary changes that benefit one sex accumulate in the newly sex-linked region. To study these questions, we analyzed the genome sequences of two seahorse species of the Syngnathidae, a fish group in which many species evolved a unique structure, the male brood pouch. We find that both seahorse species have XY sex chromosome systems, but their sex chromosome pairs are not homologs, implying that at least one turnover event has occurred. The Y-linked regions occupy 63.9% and 95.1% of the entire sex chromosome of the two species and do not exhibit extensive sequence divergence with their X-linked homologs. We find evidence for occasional recombination between the extant sex chromosomes that may account for their homomorphism. We argue that these Y-linked regions did not evolve by recombination suppression after the turnover, but by the ancestral nature of the low crossover rates in these chromosome regions. With such an ancestral crossover landscape, a turnover can instantly create an extensive Y-linked region. Finally, we test for adaptive evolution of male pouch–related genes after they became Y-linked in the seahorse.